Catholic Theological Ethics: Past, Present, and Future - Chamakala, Lucose (Asian Horizons, 2012)
James F. Keenan, ed., Catholic Theological Ethics: Past, Present, and Future. The Trento Conference, Bangalore: Theological Publications in India, 2011. Pages: xiv+337. ISBN 978-81-88821-86-0. (Originally published by Orbis Books)